Comparative Study on Performance and Design Optimization of Natural Draught Institutional Improved Cooking Stoves - Shrestha, Bijendra; Sapkota, Nishan; Adhikari, Prabidhi; Adhikari, Ashish; Basnet, Sarad; Puri, Rachan; Pariyar, Aayushman; KC, Binaya (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Biomass is one of the major sources of domestic energy in rural parts of developing countries. The use of efficient improved cooking stoves over inefficient traditional stoves plays a pivotal role in the reduction of pollutants and has a greater impact on environmental and human health. This paper aims to analyze the performance of natural draught institutional improved cooking stoves in terms of thermal efficiency and pollutant emissions. Two stoves with varying designs and dimensions were constructed and given the names Prototype I (P-I) and Prototype II (P-II). Thermal efficiency and other performance parameters were analyzed following a Water Boiling Test. The particulate matter of aerodynamic diameter less than 2.5 µm (PM2.5) and carbon monoxide (CO) were monitored for both prototypes. P-II performed better than P-I in terms of both thermal efficiency and pollutant emissions. The thermal efficiency of P-II was 31%, which was nearly 2-fold higher than that of P-I. Similarly, emissions of CO (4.6 ppm) and PM2.5 (174 µg/m3) in P-II were found to be reduced by approximately 50% and 75%, respectively. This study suggests that minor changes in design and dimension improve the performance of improved cook stoves, which may have substantial implications for energy, environment, and health.